Evidence of allocentric spatial learning in male rats with large lesions of the hippocampus - Jordan A. Webb; Sebastien Paquette; Neil M. Fournier; Michael G. Reynolds; Liana E. Brown; Hugo Lehmann (PLoS ONE, 2026)
The hippocampus (HPC) is the neural substrate of viewpoint-invariant cognitive maps, also known as allocentric spatial representations. Lesions of the HPC disrupt performance on allocentric tasks like the Morris Water Task (MWT), in which rodents must learn and recall the location of a platform submerged within a circular pool. Success in finding the hidden platform from any start point requires integrating multiple types of information, such as discerning its location relative to fixed (allocentric) environmental cues. Rats with HPC lesions, however, may show improvement in the MWT over repeated swim trials by resorting to alternative search strategies based on body-centered (egocentric) cues. Here, we investigated whether HPC lesion size correlates with allocentric impairments in the MWT. Using swim path classification alongside standard performance measures, we analyzed an archival dataset of 53 HPC lesion and 15 control rats trained under the same protocol. All rats showed evidence of learning, but the HPC group demonstrated impairment relative to the control group. Further analysis revealed that control rats shifted to a persistent allocentric search strategy by the fifth trial. The HPC rats shifted to persistent strategy use by the sixth trial, but not necessarily to an egocentric strategy. Interestingly, a subset of the HPC rats developed and maintained an allocentric strategy. Performance was not correlated with lesion size. These findings suggest that a subgroup of rats with HPC lesions, even nearly complete ones, can learn and remember allocentric spatial information in the MWT. This highlights the potential role of other brain regions in supporting spatial learning and memory in the absence of the HPC.